CUSTOMARY COURT AS ALTERNATIVE TO SETTLEMENT OF DISPUTE IN SOUTH SULAWESI - Andika Prawira Buana; Hardianto Djanggih (Diponegoro Law Review, 2018)
Customary court is a process conducted in connection with the duty to examine, to adjudicate and to decide a case in the community, which has long ago become a means to seek for justice. Customary court aims at returning broken order resulted from existing dispute. This research mainly focuses on how the essence of customary court in South Sulawesi is and how customary court serves to settle dispute in South Sulawesi. Employing socio-legal method, the research results explain that the Customary court in South Sulawesi has no longer been relied on in settlement of disputes existing in the community as the result of modern court domination.